The Analysis of Transformation of Characters into ‘Wind’ in The Alchemist and My Uncle Jamshid Khan from the Perspective of Magical Realism - Rahmat Gholami; Esmaeil Najar (پژوهشنامه ادبیات کردی, 2022)
Magical realism with its specific features, particularly the occurrence of believable magical incidents (with willing suspension of disbelief), is one of the popular genres of fictional literature, both for writers and readers of stories. Types, structures, and forms of magical realism are fostered either deliberately or unintentionally within the works and oeuvre of various authors. In this research, we examine Paulo Coelho’s novel The Alchemist and Bakhtiyar Ali’s My Uncle Jamshid Khan, Whom the Wind Always Takes Away from the standpoint of American school of comparative literature, and within the perspective of magical realism, to see how and where they compare and contrast with one another. The researchers conclude that although both of the aforementioned works utilize the technique of transforming humans into wind, and inevitable they have some similarities, they use significant takes and narratological decisions to foster their narratives in order to make their readers pursue the story.